Gangolf von Kieseritzky and the Classical Department of the Hermitage in the Last Decades of the 19th Century - Kalashnik, Yuri (Hyperboreus, 2014)
The paper describes the atmosphere that reigned at the Classical Department of the Hermitage in the 2nd half of the 19th century. This atmosphere was greatly inﬂuenced by the personalities of the three Heads of the Department of that period: L. Stephani, R.-G.-G. von Kieseritzky and E. M. Pridik.